Marketing relacional: algunos elementos por considerar para la industria del software. Caso Sysman S.A.S. (2016)
In the article one presents an offer that extends the components and implications of the concept of the Marketing to the Relational Marketing to allow him(her) new dimensions and ranges both of characterization and of measurement, besides multiple possibilities of interpretation. It (he,she) splits of tracing concepts related to the evolution and the importance that has had the marketing across the time in the performance(discharge) of the organizations, up to turning into a model of managemen. Thus, the most representative authors are taken again, doing a review of the literature in the light of the central topic. This way, one concludes that the evolution realizes of an orientation very marked to the production, later to the sale and promotion in mass finally to come to the orientation of the market that manages to strike to all the groups of interest (stakeholders), generating as consequence the model of management of Relational marketing.